Processo identitário : a metamorfose do aprender e ensinar a língua inglesa em ambiente online - Dal Prá, Alexandre Colli (2013)
This study aimed at investigating the identity practice of participants in a site dedicated to English teaching and learning called the English Experts. In order to reach this aim, this work gets theoretical support in studies of Bauman (2001, 2009), Giddens (2002), Hall (2005), Moita-Lopes (2003, 2010), Silva (2009) as sensitizing to interpret speaker’s language materializations. Purposes are to understand the process of identity construction of individuals who are dedicated to teaching and learning English in this environment, and to examine possible implications for teaching/learning practices. The research questions are: 1) How does the identity process of participants take place in the English Experts?, and 2) what implications this new environment can produce for teaching/learning that language? The research methodology is grounded in principles of interpretive or naruralistic research (ERICKSON, 1985). In order not to limit the study to pre-existing models and confine it to have traveled, seeking some insight into authors like John Ziman (1996), Moita-Lopes (2003), Thompson (2002), Uwe Flick (2009) and Zigmunt Bauman (2010), to explain how I appropriate this research approach and harmonize it to my purposes. Data were generated based on the participants’ language materialization which I collected in the site. Analysis indicates participants’ identity reacting to a new atmosphere of teaching / learning English, where knowledge, by extension, is collectively constructed and the individuals themselves must be responsible for the direction they want to build.